2019
DOI: 10.4103/ojo.ojo_221_2017
|View full text |Cite
|
Sign up to set email alerts
|

Ocular outcomes and comorbidities in preterm infants enrolled for retinopathy of prematurity screening: A cohort study from western India

Abstract: BACKGROUND:Retinopathy of prematurity (ROP) is emerging as an important cause of childhood blindness in middle-income countries such as India. Although blindness can be prevented in most cases with timely screening and treatment, certain ocular comorbidities can lead to visual impairment. We evaluated and compared 1-year visual, refractive, and structural outcomes and comorbidities in three subsets of preterm infants enrolled for screening of ROP.SUBJECTS AND METHODS:Preterm children enrolled in the hospital's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 18 publications
(20 reference statements)
0
5
0
10
Order By: Relevance
“… 83 , 84 Significant refractive errors are more common in infants with severe ROP than in those with no or mild ROP. 85 Studies comparing intravitreal anti-VEGF agents (e.g., bevacizumab and ranibizumab) with conventional lasers have shown that refractive errors are more common after laser treatment. 86 , 87 Overall, these data emphasize the importance of continual monitoring and timely intervention for vision problems in infants with significant ROP.…”
Section: Prevention Of Ropmentioning
confidence: 99%
“… 83 , 84 Significant refractive errors are more common in infants with severe ROP than in those with no or mild ROP. 85 Studies comparing intravitreal anti-VEGF agents (e.g., bevacizumab and ranibizumab) with conventional lasers have shown that refractive errors are more common after laser treatment. 86 , 87 Overall, these data emphasize the importance of continual monitoring and timely intervention for vision problems in infants with significant ROP.…”
Section: Prevention Of Ropmentioning
confidence: 99%
“…Clinical Ophthalmology 2022:16 166 retinopathy of prematurity (ROP), both in mild and severe cases. [48][49][50] The risk of developing myopia increased with increased clock hours of ROP, the higher number of laser spots, and prolonged regression times. [49][50][51] Some authors found myopia to be more common in laser-treated eyes as compared to the spontaneously regressed ROP cohorts, with cicatricial retinopathy hypothesized to be a risk factor in laser-treated eyes.…”
Section: Dovepressmentioning
confidence: 99%
“…[48][49][50] The risk of developing myopia increased with increased clock hours of ROP, the higher number of laser spots, and prolonged regression times. [49][50][51] Some authors found myopia to be more common in laser-treated eyes as compared to the spontaneously regressed ROP cohorts, with cicatricial retinopathy hypothesized to be a risk factor in laser-treated eyes. [52][53][54] In addition, the altered role of neuroectodermal components in ROP has been proposed to be a risk factor.…”
Section: Dovepressmentioning
confidence: 99%
“…[1,2] Treatments including cryotherapy and diode laser therapy have been efficacious in preventing the progression of the disease as well as decreasing the incidence of severe ocular complications such as retinal detachment and eventual visual loss. [3][4][5] Since about 1990, diode laser photocoagulation has been considered a therapeutic option with better visual outcomes than cryotherapy. [6] Furthermore, argon laser therapy has also been used for patients with threshold ROP for about two decades.…”
Section: Introductionmentioning
confidence: 99%